2003
DOI: 10.1007/s00432-003-0499-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cdx2 and the phenotype of advanced gastric cancers: relationship with prognosis

Abstract: Our results suggest that Cdx2 is a useful prognostic marker. In addition, advanced gastric cancers with both intestinal and gastric phenotypic expression have a relatively good prognosis. Combined evaluation of gastric and intestinal epithelial cell markers, including Cdx2, is clinically useful to predict outcome in patients with advanced neoplasm of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
147
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(169 citation statements)
references
References 40 publications
16
147
3
3
Order By: Relevance
“…For phenotypic expression analysis of GC, we performed immunohistochemical analysis (as described above) with 4 antibodies: anti-MUC5AC (Novocastra, Newcastle, UK) as a marker of foveolar epithelial cells in the stomach, anti-MUC6 (Novocastra) as a marker of pyloric gland cells in the stomach, anti-MUC2 (Novocastra) as a marker of goblet cells in the small intestine and colorectum and anti-CD10 (Novocastra) as a marker of microvilli of absorptive cells in the small intestine and colorectum. The criteria 19 for the classification of G type and I type GCs were as follows. GCs in which more than 10% of cells in the section expressed at least 1 gastric epithelial cell marker (MUC5AC or MUC6) or intestinal epithelial cell marker (MUC2 or CD10) were classified as G type or I type cancers, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For phenotypic expression analysis of GC, we performed immunohistochemical analysis (as described above) with 4 antibodies: anti-MUC5AC (Novocastra, Newcastle, UK) as a marker of foveolar epithelial cells in the stomach, anti-MUC6 (Novocastra) as a marker of pyloric gland cells in the stomach, anti-MUC2 (Novocastra) as a marker of goblet cells in the small intestine and colorectum and anti-CD10 (Novocastra) as a marker of microvilli of absorptive cells in the small intestine and colorectum. The criteria 19 for the classification of G type and I type GCs were as follows. GCs in which more than 10% of cells in the section expressed at least 1 gastric epithelial cell marker (MUC5AC or MUC6) or intestinal epithelial cell marker (MUC2 or CD10) were classified as G type or I type cancers, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Determination of ABI Anaphase bridges were scored as described previously (Seno et al, 2002;Aoki et al, 2003;Mizoshita et al, 2003;Supplementary Information).…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
“…23 CDX2 expression is associated with not only intestinal mucin phenotypes, 14,24 but also an early tumor stage [24][25][26][27][28][29][30] and improved prognosis in patients with gastric cancer. [29][30][31][32] A previous study reported that CDX2 expression is also correlated with an improved prognosis in patients with ampullary adenocarcinomas. 33 Several previous studies have compared the protein expression profiles of gastric and colonic carcinomas and small intestinal adenocarcinomas because of the anatomical proximity and similarities between these cancers.…”
mentioning
confidence: 99%